PENCATATAN KEUANGAN SD IT LUHURING BUDI KELURAHAN AGROWISATA KECAMATAN RUMBAI BARAT - Salmiah, Neneng; Wiyati, Rita; Wibisono, Rafidianto; Februari, Aura Cinta (Komunitas Manajemen Kompetitif, 2024)
Luhuring Budi Integrated Islamic Elementary School (SD IT) is one of the 6-year program educational institutions that not only provides education based on the national curriculum but also prioritizes Islamic education with the aim of producing graduates who are knowledgeable and have noble morals. The operation of SD IT Luhuring Budi not only comes from the School Assistance Fund (BOS) but also comes from routine student guardian contributions (SPP), development fees, uniform fees, and student shuttle bus fees. The payment of these contributions can be made in cash or in installments and some of the payments are through the homeroom teacher and some directly to the finance department. Based on the results of the interview of the FEB PKM Team with the Principal of SD IT Luhuring Budi, information was obtained that the principal needed information on the amount of bills (accounts receivable) and cash balances in real time. However, the human resources of SD IT Luhuring Budi (finance department and homeroom teacher) do not have an educational background in the Accounting Field so they do not have knowledge about financial records. Therefore, the Community Service Team of FEB Unilak Lecturers is motivated to provide financial recording knowledge at SD IT Luhuring Budi which aims to improve the knowledge of finance and homeroom teachers so that in the future they can do financial recording according to Accounting Science and can provide the information needed. The methods used are conducting pre-tests, material delivery, training, questions and answers, and post tests. The results achieved from this PKM activity were obtained from the comparison of post test results with pre-test results. The results of the comparison of the post test with the results of the pre-test showed that before the PKM, the Finance Section and the Homeroom Teacher of SD IT Luhuring Budi had financial knowledge but was not in accordance with Accounting Science. In other words, the knowledge of financial recording is still low. After PKM, there is an increase in financial recording knowledge in accordance with Accounting Science, especially recording using special journals. Keywords: Financial Recording, SD IT Luhuring Budi